Artificial Intelligence, Cultural Intelligence and Spiritual Intelligence in the Political Culture - Frunză, Sandu (Journal for the study of religions and ideologies, 2026)
The political culture of the digital age brings with it new challenges. On the one hand, we are exposed to a new dynamic and a change of perspective brought to political communication by the intervention of Artificial Intelligence and the increasingly significant role played by virtual space and social networks. On the other hand, the demands of the promoters of Cultural Intelligence and Spiritual Intelligence to remain in the main trend of local and global political practices are intensifying. We analyzed the relationship between Cultural Intelligence, Spiritual Intelligence and Artificial Intelligence within political culture. The three forms of intelligence are convergent. With the development of communication technologies and social networks, Artificial Intelligence, even if it cannot act as a moral agent, determines a radical change in terms of the structuring of political communication, influencing strategies and mechanisms for generating content regarding values ​​and meaning. Cultural Intelligence, understood as the ability to adapt effectively to multicultural contexts and diversity, plays an important role in the pluralistic and axiological practices of democratic society. Spiritual Intelligence, understood as the ability to reflect on the meaning of life, values ​​and transcendence, to generate responsibility and moral legitimacy, can contribute to relationships based on authenticity in political practices. In the digital age, the convergence between Cultural Intelligence and Spiritual Intelligence contributes to overcoming ethnocentrism, fundamentalism and extremism, to recognizing the values ​​of otherness and respect for diversity, to cultivating pluralism, dialogue and the common good in the practices of democratic political culture.